Physical working capacity as a health indicator and its relation to the occurrence of "infinite tone" phenomenon in soccer players - Mykhaliuk, Ye. L.; Horokhovskyi, Ye. Yu.; Bosenko, A. I.; Orlyk, N. A.; Михалюк, Євген Леонідович; Гороховський, Є. Ю.; Босенко, А. І.; Орлик, Н. А. (My University, 2024)
The aim of the research was to determine the relationship between the occurrence of dystonic type response to dosed physical activity in soccer players depending on physical work capacity as an indicator of health. Material and Methods. A total of 741 soccer players were studied, ranging from 3rd class athlete to Master of Sports of International Class (MSIC). The players were compared according to their sports qualification and the presence or absence of the "infinite tone" phenomenon. Blood pressure was measured by the Korotkov method using a Romed sphygmomanometer (Holland). Physical work capacity was assessed on a Corival ergometer according to the method of V.L. Karpman (1988). Results. It was found that physical work capacity did not have significant differences in soccer players with "infinite tone" and without it, except for soccer players with sports qualification CMS-1st class athlete, in whom it was greater. Thus, relatively high values of physical work capacity in soccer players with sports qualification MS-MSIC and 2nd-3rd class athlete with and without "infinite tone", and also significantly greater — in soccer players with sports qualification CMS-1st class athlete do not allow to consider the cause of this phenomenon in athletes as overtraining or as a result of exhausting physical activity. Резюме. Мета дослідження – визначити взаємозв’язок між виникненням дистонічного типу реакції на дозоване фізичне навантаження у футболістів залежно від фізичної працездатності як показника здоров’я. Матеріал і методи. Всього було досліджено 741 футболіста, від спортсмена 3-го розряду до майстра спорту міжнародного класу (MСМК). Гравців порівнювали за їхньою спортивною кваліфікацією та наявністю чи відсутністю феномену «нескінченного тону». Артеріальний тиск вимірювали за методом Короткова на сфігмоманометрі Romed (Голландія). Фізичну працездатність оцінювали на велоергометрі Corival за методикою В.Л. Карпмана (1988). Результати. Встановлено, що фізична працездатність не мала достовірних відмінностей у футболістів з «нескінченним тоном» і без нього, за винятком футболістів зі спортивною кваліфікацією КМ – спортсмен 1 розряду, у яких вона була більшою. Так, відносно високі показники фізичної працездатності у футболістів зі спортивною кваліфікацією MС – MСМК і спортсменів 2–3 розряду з «нескінченним тоном» і без нього, а також значно більші — у футболістів зі спортивною кваліфікацією спортсмен КМС – 1 розряд. дозволяють вважати причиною цього явища у спортсменів перетренованість або наслідок виснажливих фізичних навантажень.
Фізична працездатність як показник здоров’я та її зв’язок з виникненням феномену «нескінченного тону» у футболістів
Keywords: football players; sports qualification; infinite tone; PWC170 test; physical work capacity; футболісти; спортивна кваліфікація; нескінченний тон; тест PWC170; фізична працездатність